Efektivitas Promosi Digital dalam Menarik Generasi Milenial dan Z - Sri Lestari (PUTRA JAWA PUBLISHER, 2024)
This research discusses the effectiveness of digital promotions in attracting Millennials and Z generations as the dominant target market in the digital era. With the increasing use of technology and social media, companies need to adopt relevant marketing strategies to reach these segments. This research uses a qualitative method with data collection techniques through in-depth interviews and related literature studies. The results show that digital promotion has a significant role in shaping Millennials' and Z generations' perceptions and interest in products or services. Factors such as interactive content, use of influencers, and personalization of marketing messages are proven to increase customer engagement and loyalty. Social media such as Instagram, TikTok, and YouTube are becoming the most effective platforms in digital marketing campaigns. However, challenges include rapidly changing trends, high levels of competition, and the need for constant innovation. With the right strategy, companies can maximize the potential of digital promotions to achieve long-term success.